High Performance Computing in Science and Engineering ’01: Transactions of the High Performance Computing Center Stuttgart (HLRS) 2001 - Krause, Egon; Jäger, Willi (Springer, 2002)
The state of the art in supercomputing is summarized in this volume. The book presents selected results of the projects of the High Performance Computing Center Stuttgart (HLRS) for the year 2001. Together these contributions provide an overview of recent developments in high performance computing and simulation. Reflecting the close cooperation of the HLRS with industry, special emphasis has been put on the industrial relevance of the presented results and methods. The book therefore becomes a collection of showcases for an innovative usage of state-of-the-art modeling, novel numerical algorithms and the use of leading edge high performance computing systems in a GRID-like environment
Keywords: Aufsatzsammlung